Perforation repair with artificial floor technique - A microleakage study - Pradeep Chaudhari; Vasundhara Shivanna (Wolters Kluwer Medknow Publications, 2009)
In endodontic practice one of the most common procedural accident is furcation perforation. Many materials and techniques have been tried to repair the furcation perforation. The purpose of this study is to evaluate the effect of calcium sulfate and hydroxylapatite matrix on the sealing ability of resin modified glass ionomer cement to repair the furcation perforation. The result of the study showed that the microleakage was least when perforation was repaired with resin modified glass ionomer cement over hydroxylapatite used as an internal matrix. And it was maximum when perforation was repaired with resin modified glass ionomer cement without any internal matrix material.